(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
Unwanted loneliness among young people and older adults is a significant challenge in today’s societies. The University of Valladolid (UVa), as an educational institution, is currently developing an intergenerational project to foster connections between older adults and university students. The program is carried out in collaboration with the Services Department of the Regional Government of Castile and León and the city councils of the four UVa campuses. The project is structured around various social action programs aimed at older adults and university students. Its main tools and best practices include: shared housing, solidarity apartments, intergenerational classrooms, intergenerational volunteering, and a service-learning project.